Pengembangan Film Animasi Berbasis Nilai Budaya Pela Gandong di SDN 1 Masohi - Ahsani Amalia Anwar; Alvionita Dahoklory (STKIP Andi Matappa Pangkep, 2022)
The aim of the study is to develop an animated film as learning media based on the cultural value of Pela Gandong as a thematic education medium for K-13 theme 1 sub-theme 1 Cultural diversity in Civics. The study applied Research and Development (R&D) method. The data were collected through questionnaires and class tests. Aspects of material assessment include aspects of the suitability of the material with the core curriculum and basic curriculum 3.4. From a media perspective, including technical quality, narration, music/sound effects. The teacher assessed that the animated film category was very appropriate, the learning aspect, and the audio aspect of animated film media shows were all in the good category. The material test for the animated film